'I am big; he is little': interrogating the effects of developmental discourses among children in inclusive early childhood classrooms. Issue 2 (3rd April 2022) - Watson, Karen
ABSTRACT : Over past decades in early childhood education, there has been an emerging critique of developmental discourses. Despite this, the universality of child development theory persists and along with it, expectations of a linear progression via prescribed stages and ages. Developmentalism produces a normal in the classroom that sanctions comparisons, positioning any difference to the normal as problematic. In this paper, using observation and conversation data from a larger poststructural ethnographic study of three inclusive early childhood classrooms in Australia, the effects of developmental discourses on the classroom and on inclusive practice are examined. Providing an alternative view of inclusion, the paper focuses on the operations of the normal, exposing the exclusionary effects of developmental discourses on children, and among children. As children negotiate difference in the classroom, they draw on sanctioned developmental understandings in coming to know themselves and others. Interrupting the power and authority of these discourses and the way they produce certain ways of being and becoming could provide some promise for inclusive practices.